Nano-drug co-delivery system of natural active ingredients and chemotherapy drugs for cancer treatment: a review - Bingqian Li; Huili Shao; Lei Gao; Huan Li; Huagang Sheng; Liqiao Zhu (Taylor & Francis Group, 2022)
Chemotherapy drugs have been used for a long time in the treatment of cancer, but serious side effects are caused by the inability of the drug to be solely delivered to the tumor when treating cancer with chemotherapy. Natural products have attracted more and more attention due to the antitumor effect in multiple ways, abundant resources and less side effects. Therefore, the combination of natural active ingredients and chemotherapy drugs may be an effective antitumor strategy, which can inhibit the growth of tumor and multidrug resistance, reduce side effects of chemotherapy drugs. Nano-drug co-delivery system (NDCDS) can play an important role in the combination of natural active ingredients and chemotherapy drugs. This review provides a comprehensive summary of the research status and application prospect of nano-delivery strategies for the combination of natural active ingredients and chemotherapy drugs, aiming to provide a basis for the development of anti-tumor drugs.